1987
DOI: 10.1111/j.1432-1033.1987.tb10668.x
|View full text |Cite
|
Sign up to set email alerts
|

Glyceraldehyde‐phosphate dehydrogenase from Trypanosoma brucei

Abstract: Trypanosoma bruceicontains two glyceraldehyde-phosphate (GAPDH; EC 1.2.1.12) isoenzymes; one is located in glycosomes and represents 80% of the total activity, whereas the other is present in the cytosol. The purification of the cytosolic GAPDH, which is identical in both bloodstream-form and insect-stage trypanosomes, is described, and the enzyme compared with its glycosomal counterpart. Cytosolic GAPDH is specific for NAD. It is a tetrameric enzyme with subunits of 33.5 kDa, 5 kDa smaller than those of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Fig. 1 in the accompanying paper [14]) [8] and [9]. However, the amount of PGK which is soluble in insect trypanosomes varies from experiment to experiment: 91 % in Opperdoes et al [9] against 59% here (cf.…”
Section: Sedimentation Velocity Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Fig. 1 in the accompanying paper [14]) [8] and [9]. However, the amount of PGK which is soluble in insect trypanosomes varies from experiment to experiment: 91 % in Opperdoes et al [9] against 59% here (cf.…”
Section: Sedimentation Velocity Analysismentioning
confidence: 99%
“…Since we had previously purified the glycosomal enzymes using phenylSepharose chromatography and therefore knew their exact elution positions, we decided to use this technique for the purification of cytosolic isoenzymes as well (see also the accompanying paper [14]). Fig.…”
Section: Purification Of the Cytosolic Isoenzyme Of Phosphoglycerate mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of these proteins are encoded by different genes (Sullivan et al 1985, Huang et al 1989) and the glycosomal enzymes are synthesised in the cytoplasm by free ribosomes and imported post-translationally without apparent cleavage or modification. Several of these glycosomal and cytosolic isoenzymes have been purified from T. brucei (Misset et al 1986(Misset et al , 1987 and T. cruzi (Bourguignon et al 1997) and were distinguished structurally from their mammalian counterparts (Michels & Opperdoes 1991). In view of this and based on the observation that the inhibition of some glycosomal enzymes from T. brucei (Durieux et al 1991) may result in the death of the parasite (Opperdoes et al 1990, Willson et al 1993) these enzymes have suggested as promising targets for drug design.…”
mentioning
confidence: 99%